Gestión de ventas en la Empresa “Mini Market Xavier Rueda 24/7” en la ciudad de Babahoyo en el período 2023. - Rojas Reyes, Robert Jhossep (2024)
Mini Market Xavier Rueda 24/7, located in Babahoyo, Ecuador, was founded in 2003 to meet the growing demand for essential products in the community. Despite its positioning as a key supplier, the company faces several challenges that affect its operability and ability to grow. Among these challenges are significant deficiencies in sales management, lack of strategic planning, ineffective advertising strategies and problems in customer service. Inefficient inventory management has led to stock-outs and over-inventories, compromising product availability and operational efficiency. The absence of modern technology tools for sales management and data analysis has made it difficult to identify and proactively resolve critical issues, affecting the long-term sustainability of the business. In addition, the company has received complaints about the quality of products, including expired or spoiled products, which negatively affects the customer experience and the reputation of the store. The present study focuses on improving the economic income of Mini Market Xavier Rueda 24/7 by implementing more effective strategies and administrative management processes. These improvements are expected to optimise internal operation and strengthen competitiveness in the local market. Among the techniques to be used are the optimization of resources, improvement in financial planning and the implementation of more rigorous control systems. The study also seeks to highlight the benefits of proper quality management, improving daily operational activities and allowing better product traceability. Active collaboration between owner and staff will facilitate data collection and ensure the relevance of the results obtained. The findings will not only be applied to improve quality management in Mini Market Xavier Rueda 24/7, but will also serve as a reference for future research in companies facing similar challenges, seeks to highlight the benefits of proper quality management, improving daily operational activities and allowing better product traceability. Active collaboration between owner and staff will facilitate data collection and ensure the relevance of the results obtained. The findings will not only be applied to improve quality management at Mini Market Xavier Rueda 24/7, but will also serve as a reference for future research in companies facing similar challenges.